UPAYA PENANGGULANGAN TERHADAP TINDAK PIDANA PERDAGANGAN ORANG DI KABUPATEN BULELENG (STUDI KASUS DI KANTOR IMIGRASI KELAS II TPI SINGARAJA) - I Made Lanang Sudarmayana (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2025)
This research aims to ( 1 ) determine and analyze the efforts to overcome the crime of human trafficking by the Singaraja Immigration Office in Buleleng regency. To ( 2 ) determine and analyze the obstacles experienced by the Singaraja Calss II TPI Immigration Office in overcoming the crime of human trafficking in Buleleng regency. This study uses empirical legal research, specifically using a descriptive approach. The data and data sources used in this study include primary data dan secondary data, where secondary data consists of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection techniques used include document study techniques, observation techniques, and interview techniques. The technique used the determine the research sample is a non-probability sampling approach, especially the purposive sampling technique for selecting research subjects. After that the data obtained, processed, and analyzed qualitatively. The results of the stufy show ( 1 ) efforts to overcome the crime of human trafficking at the Singaraja Class II Immigration Office are carried out preventively through passport issuance procedures, socialyzation of the community, through the Immigration Forstered Village launch program. Then repressively through collaboration with other law onforcement agencies, working together in the field of investigation. ( 2 ) obstacles in implementing the handling of the crime of Human Trafficking at the Singaraja Class II TPI Immigration Office, namely the lack of human resources at the Singaraja Immigration so that the implementation of the program is not optimal, lack of public knowledge regarding the crime of human trafficking.